2015
DOI: 10.1097/mcc.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the use of multimodal monitoring in the neurointensive care unit

Abstract: MMM allows comprehensive exploration of the complex pathophysiology of acute brain damage and, depending on the different configuration of the pathological condition we are treating, the application of targeted individualized care. Unfortunately, we still lack robust evidence on how to better integrate MMM-derived information at the bedside to improve patient management. Advanced informatics is promising and may provide us a supportive tool to interpret physiologic events and guide pathophysiological-based the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 65 publications
(58 reference statements)
1
63
0
1
Order By: Relevance
“…Outcome (eGOS) at six months was available in 28 patients. The median outcome was poor (3 [1,6]), and 13 of the 28 patients died. Figure 3 shows the time courses of the TDDDs, mean baseline p ti O 2 , mean baseline CPP, mean baseline MAP, mean baseline ICP, and mean baseline brain temperature over the first 11 days after the initial hemorrhage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome (eGOS) at six months was available in 28 patients. The median outcome was poor (3 [1,6]), and 13 of the 28 patients died. Figure 3 shows the time courses of the TDDDs, mean baseline p ti O 2 , mean baseline CPP, mean baseline MAP, mean baseline ICP, and mean baseline brain temperature over the first 11 days after the initial hemorrhage.…”
Section: Resultsmentioning
confidence: 99%
“…1 The most widely used measures are currently intracranial pressure (ICP), brain perfusion, brain oxygen availability (measured as tissue partial pressure of oxygen [p ti O 2 ]) and scalp electroencephalography (EEG) or, respectively, invasive electrocorticography (ECoG).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown variable levels for management of neuronal trauma. Our survey shows that the EVD is the preferred technique for ICP monitoring in patients with traumatic brain injury (16)(17)(18)(19)(20)(21). We found that using techniques such as Ghajar Guide is infrequent, perhaps because of the high cost of this system in a country with limited resources such as Colombia.…”
Section: Discussionmentioning
confidence: 90%
“…Sophisticated haemodynamic monitoring systems are involved, including mechanisms of data acquisition and analysis. Needless to say, the challenge will be the real-time interpretation and integration into individualised targeted therapy regimens 65. However, it is important to highlight that despite over 10 years of use in neurocritical intensive care, robust evidence on how to better integrate multimodal monitoring-derived information at the bedside to improve patient management is lacking.…”
Section: Multimodal Monitoring and Decision Support Systemsmentioning
confidence: 99%